Near-surface geophysics - Butler, Dwain K. (Investigations in geophysics, 2005)
Presents concepts and fundamentals of near-surface geophysics in Part 1 and applications and case histories in Part 2. Dedicated to Stanley H. Ward, Near-Surface Geophysics updates and extends the scope of his landmark three-volume book, Geotechnical and Environmental Geophysics, published by SEG in 1990. Part 1 of Near-Surface Geophysics contains innovative material on magnetic and electrical methods, subsurface geophysics, near-surface seismology, emphasizes the determination of physical properties, the prevalence of multimethod surveys and integrated interpretations, and the increasing use of model-based survey planning, execution, and interpretation. Near-Surface Geophysics, a peer-reviewed hardcover book of 732 pages, will be of interest to practitioners and students.